Etiologia i patomechanizm uszkodzenia ścięgna Achillesa = The etiology and patomechanizm damage to the Achilles tendon - Strojek, Katarzyna; Piekorz, Zuzanna; Kaźmierczak, Urszula; Strączyńska, Agnieszka; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Strojek Katarzyna, Piekorz Zuzanna, Kaźmierczak Urszula, Strączyńska Agnieszka, Zukow Walery. Etiologia i patomechanizm uszkodzenia ścięgna Achillesa = The etiology and patomechanizm damage to the Achilles tendon. Journal of Education, Health and Sport. 2016;6(11):147-160. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164687 http://ojs.ukw.edu.pl/index.php/johs/article/view/3976 https://pbn.nauka.gov.pl/sedno-webapp/works/755729 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 03.11.2016. Etiologia i patomechanizm uszkodzenia ścięgna Achillesa The etiology and patomechanizm damage to the Achilles tendon Katarzyna Strojek¹, Zuzanna Piekorz¹, Urszula Kaźmierczak¹, Agnieszka Strączyńska¹, Walery Zukow2 1. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 2. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska Słowa kluczowe: ścięgno Achillesa. Keywords: Achilles tendon. Streszczenie Uszkodzenie ścięgna Achillesa stanowi bardzo poważny problem kliniczny, ponieważ uniemożliwia pacjentowi prawidłowe funkcjonowanie, a tym samym przyczynia się do ograniczenia jakości życia. W światowej literaturze zagadnienia związane z leczeniem oraz usprawnianiem pacjentów po przerwaniu ścięgna Achillesa pojawiają się bardzo często. W dzisiejszych czasach nastąpił znaczny wzrost zainteresowania uprawianiem sportu, zwłaszcza w warunkach rekreacyjnych, niestety jest to również związane z różnorodnymi oraz częstszymi urazami w obrębie narządu ruchu. Jednym z nich jest uszkodzenie ścięgna Achillesa, uznawane obecnie za chorobę cywilizacyjną. Summary Damage to the Achilles tendon is a serious clinical problem, because it prevents the proper functioning of the patient, and thus contributes to reducing the quality of life. In the world literature issues associated with treatment and improve patients after cessation of the Achilles tendon appear very often. In modern times there has been a significant increase in the interest in having the sport, especially in terms of recreation, unfortunately it is also associated with various and frequent injuries within the musculoskeletal system. One of them is the damage to the Achilles tendon, now considered the civilization disease.